Racial disparities negatively impact outcomes in early‐onset colorectal cancer independent of socioeconomic status. (14th October 2021) - Kamath, Suneel D.; Torrejon, Nataly; Wei, Wei; Tullio, Katherine; Nair, Kanika G.; Liska, David; Krishnamurthi, Smitha S.; Khorana, Alok A.
Abstract: Background: The incidence of colorectal cancer (CRC) in patients under age 50 is rising for unclear reasons. We examined the effects of socioeconomic factors on outcomes for patients with early‐onset CRC compared to late‐onset CRC. Methods: Patients with CRC from 2004 to 2015 in the National Cancer Database were included and categorized by age (under or over 50 years). Differences in demographic and socioeconomic factors, disease characteristics, and survival outcomes between early‐onset versus late‐onset CRC patients were assessed by Chi‐squared test and Cox models. Results: The study population included 1, 061, 204 patients, 108, 058 (10.2%) of whom were under age 50. The proportion of patients diagnosed under age 50 increased over time: 9.4% in 2004–2006, 10.1% in 2007–2009, 10.5% in 2010–2012, and 10.7% in 2013–2015 ( p  < 0.0001). Early‐onset CRC patients were more likely to be Black (15.1% vs. 11.3%) or Hispanic (8.6% vs. 4.6%) and to present with stage 4 disease (24.9% vs. 17.0%), p  < 0.0001 for all. Black patients had the worst median OS (58.3 months) compared to White (67.0 months), Hispanic (91.6 months), or Asian (104.9 months) patients, p  < 0.0001. Within the subgroup of early‐onset CRC patients with private insurance, Black patients had worse OS compared to White patients, even in communities with higher income and education status. Conclusions: Early‐onset CRC continues to increase. Patients with early‐onset CRC are more likely to be Black or Hispanic and to present with stage 4 cancer. Early‐onset Black patients showed worse OS compared to White patients in all income subgroups, even with private insurance. Abstract : Patients with early‐onset colorectal cancer are more likely to be Black or Hispanic and to present with stage 4 cancer. Within the subgroup of early‐onset CRC patients with private insurance, Black patients had worse OS compared to White patients, even in communities with higher income and education status.